Prospective study on the attitude toward school of secondary school students in the post-pandemic period - Popa, Eleonora Mihaela (Technium Social Sciences Journal, 2022)
This paper is aimed to study the attitude of secondary school students towards school. The research was conducted on a sample of 437 secondary school students and 42 teachers, who teach them. Students were given a questionnaire to identify their attitude towards school from five perspectives: students' self-perception from an academic point of view, students' attitude towards the school itself, attitude towards teachers, the importance they attach to goals, motivation, and self-regulation. Group interviews with teachers explored the relationship between teachers and students, how teachers relate to students, how they perceive students, how school assessments are done, how they provide feedback to students, as well as issues of improving students' attitudes towards school. The results of the study revealed certain associations between students' attitudes towards school and teachers' perception of it.